Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Harga Saham pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Indra Dekrijanti; Muhammad Bawono; Istan Wighara Moelyono; Yanti Vela Yudiana (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2023)
Abstract: This study aims to determine the influence of investment decisions, funding decisions and dividend policies on stock prices carried out by banking companies listed on the Indonesia Stock Exchange. The population of this study is banking companies listed on the IDX in 2021-2022. This type of research uses quantitative with a causal associative approach. The population in this study is all banking companies listed on the Indonesia Stock Exchange. The sample was determined based on the purposive sampling method, as many as 105 companies. The results showed that (1) investment decisions had a negative and significant effect on stock prices, (2) funding decisions had no effect on stock prices, (3) dividend policies had no effect on stock prices, (4) investment decisions, funding decisions and dividend policies simultaneously had a positive and significant effect on stock prices.